2008
DOI: 10.1128/aem.02348-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wastewater Treatment Plant Effluent on Microbial Function and Community Structure in the Sediment of a Freshwater Stream with Variable Seasonal Flow

Abstract: We investigated the effects of wastewater treatment plant (WWTP) discharge on the ecology of bacterial communities in the sediment of a small, low-gradient stream in South Australia. The quantification of genes involved in the biogeochemical cycling of carbon and nitrogen was used to assess potential impacts on ecosystem functions. The effects of disturbance on bacterial community structure were assessed by PCRdenaturing gradient gel electrophoresis of 16S rRNA genes, and clone library analysis was used to phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
133
6
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(151 citation statements)
references
References 50 publications
9
133
6
3
Order By: Relevance
“…Toxic compounds could also explain the observed increases in per-cell respiration rates, as previous studies indicated that respiration rates normalized by biomass increase for bacterial cells that are under stress (47). Toxic compounds in the effluent could also contribute to the decreases in bacterial diversity and species richness at the downstream sites, which conflicted with previously reported findings that demonstrated an increase in bacterial diversity downstream of a WWTP effluent input (9). Although quantification of toxic compounds in the effluents was beyond the scope of this study, future explorations of this topic are warranted.…”
Section: Fig 5 Shannon Diversity Index (A) and Chao 1 Richness Estimacontrasting
confidence: 56%
See 2 more Smart Citations
“…Toxic compounds could also explain the observed increases in per-cell respiration rates, as previous studies indicated that respiration rates normalized by biomass increase for bacterial cells that are under stress (47). Toxic compounds in the effluent could also contribute to the decreases in bacterial diversity and species richness at the downstream sites, which conflicted with previously reported findings that demonstrated an increase in bacterial diversity downstream of a WWTP effluent input (9). Although quantification of toxic compounds in the effluents was beyond the scope of this study, future explorations of this topic are warranted.…”
Section: Fig 5 Shannon Diversity Index (A) and Chao 1 Richness Estimacontrasting
confidence: 56%
“…Several previous studies have also examined the effects of WWTP effluent on bacterial populations within the water column (6)(7)(8), and some have demonstrated the ability of microorganisms contained in the effluent to persist in the water column of the receiving system (8). However, few studies have examined the potential effects of WWTP effluent on benthic microbial communities (9) despite the fact that bacterial numbers are generally much higher in freshwater sediment than in the overlying water (10) and despite the fact that benthic microbial communities are critical components of lotic ecosystems, as they contribute to organic matter decomposition, nutrient cycling, and bioremediation of a variety of pollutants. Several recent studies have presented evidence that WWTP effluent may impact the function and structure of sediment microbial communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, wetland plant rhizosphere microbial characteristics can sensitively reflect the status of plant and water quality, which are considered ideal indicators of aquatic ecosystems and have been extensively used to assess the degree of toxicity imposed by various pollutants. To the best of our knowledge, most studies have focused on the impacts of wastewater treatment plants (WWTPs) effluent on bacterial communities in the water column and sediment of receiving river (Wakelin et al, 2008;Drury et al, 2013). But few studies have investigated wetland plant rhizosphere bacteria community under reclaimed water disturbance condition.…”
Section: Introductionmentioning
confidence: 99%
“…In wastewater treatment systems, aeration has typically been used to activate the biochemical oxidation of organic compounds, sulfide, ammonia, and nitrite [7,31,35,37], but it is a highly costly process. Wastewater treatment using an MFC may be a less energy-dependent but less efficient process than an aeration-dependent system.…”
mentioning
confidence: 99%